Pokémon. Sword & shield. Volume 11 - Kusaka, Hidenori; Tanzer, Molly (VIZ Media, LLC, 2024)
"Henry and Casey continue to search for the lost Rusted Sword and Rusted Shield as Henry trains the Kubfu, the Pokémon from the Isle of Armor. But a new danger presents itself..."--back cover.